Monitoreo De Pasos De Fauna Silvestre Y Su Uso En El Corredor Vial Villavicencio-Yopal (2022)
Since 2020, in the Villavicencio-Yopal road corridor, the construction of aerial wildlife crossings began, in places identified as critical runover points, these are a tool for mitigating impacts due to road development. Within this context, camera trapping can be a fundamental technique, since it allows observing the interaction of different animal species with the passages of fauna and demonstrating its use by species. This study sought to evaluate by means of camera traps the use of aerial fauna passages by wild species in the area, the frequency of crossing and the variables that influence it. The road corridor is located between Villavicencio-Meta to Yopal-Casanare, it has a length of 260 km. There are currently 18 aerial fauna crossings built that connect forested areas, 12 were monitored from June to December 2021. The cameras were installed in nearby trees in the direction of the crossing or directly on the structure, turned on for 24 hours, active 30 days. , in video mode 15 sec or photo with an interval of 3 sec between one record and another. The steps are metallic structures with a height between 11 and 14 meters, they have a catwalk with a chain link mesh of a length of approximately 30 to 80 meters long and a resistance capacity according to the established norm. During this period, 350 records of use were found in 7 of the monitored steps, species such as Saimiri cassiquiarensis were identified with a relative crossing frequency of 92%, Caluromys lanatus 6% and Dactylomys dactylinus and Didelphis marsupialis 1% each. The variables that influence the use of these structures were evaluated, such as elevation, location, distance from the passage to the body of water and distance from the passage to the road. This study demonstrates that this strategy works as a mitigation alternative, improving the connectivity of fragmented forest areas, crossings of wildlife through the roads without putting their lives at risk, and additionally allows to see the influence of environmental variables, the passage and the route in the frequency of use.